The promise and the reality: a mental health workforce perspective on technology-enhanced youth mental health service delivery. Issue 1 (December 2016) - Orlowski, Simone; Lawn, Sharon; Matthews, Ben; Venning, Anthony; Wyld, Kaisha; Jones, Gabrielle; Winsall, Megan; Antezana, Gaston; Schrader, Geoffrey; Bidargaddi, Niranjan
Abstract Background Digital technologies show promise for reversing poor engagement of youth (16–24 years) with mental health services. In particular, mobile and internet based applications with communication capabilities can augment face-to-face mental health service provision. The literature in this field, however, fails to adequately capture the perspectives of the youth mental health workforce regarding utility and acceptability of technology for this purpose. Methods This paper describes results of in-depth qualitative data drawn from various stakeholders involved in provision of youth mental health services in one Australian rural region. Data were obtained using focus groups and semi-structured interviews with regional youth mental health clinicians, youth workers and support/management staff (n  = 4 focus groups;n  = 8 interviews) and analysed via inductive thematic analysis. Results Results question the acceptability of technology to engage clients within youth mental health services. Six main themes were identified:young people in a digital age, personal connection, power and vulnerability, professional identity, individual factors andorganisational legitimacy . Conclusions These findings deepen the understanding of risks and challenges faced when adopting new technologies in mental healthcare. Recommendations for technology design and implementation in mental health services are made.